The changing prevalence of asthma - Jarvis, Deborah (Henry Stewart Talks, 2011)
Measuring asthma prevalence in community studies, Geographical variation in prevalence of disease, Early studies showing an increase in disease, More recent studies of time trends, Possible reasons for changing prevalence of disease